Análise da percepção do grau de importância e implantação dos elementos do Quick Response Manufacturing em uma empresa do setor de cosméticos: um estudo exploratório - Cardoso, Ronney Teixeira (2019)
The Quick Response Manufacturing (QRM) is an alternative management approach to Lean Manufacturing, which aims to achieve lead time reduction in environments with a high variety of products. The objective of the present research is to evaluate the degree of knowledge and application of QRM in a company of the cosmetics sector and, from this, to propose improvement actions so that companies can better prepare to introduce QRM in their business. Basically the proposal followed the basic steps of a QRM project, reaching the conclusion that the long lead time in the studied sector of the company is caused by four main causes: (I) high demand for orders that are not being served within a lead time four weeks; (Ii) lack of adequate processes in the project sector; (III) delay in the arrival of machinery; and (IV) difficulty in implementing the QRM mentality in departments such as Purchasing and Finance. It was possible to conclude from this that managing the changes in the QRM implementation process is a fundamental factor in order to take advantage of the benefits brought by this approach, making it important for companies to invest in QRM training and dissemination and awareness of employees, suppliers and customers about this approach, since the research made it clear that employees understand the importance of lead time, but need support, training, direction and integrated vision that must be provided by top management.